2012
DOI: 10.1002/open.201200031
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition in Glycolaldehyde, the Simplest Sugar: Two Isolated Hydrogen Bonds Win Over One Cooperative Pair

Abstract: Carbohydrates are used in nature as molecular recognition tools. Understanding their conformational behavior upon aggregation helps in rationalizing the way in which cells and bacteria use sugars to communicate. Here, the simplest α-hydroxy carbonyl compound, glycolaldehyde, was used as a model system. It was shown to form compact polar C2-symmetric dimers with intermolecular O–H⋅⋅⋅O=C bonds, while sacrificing the corresponding intramolecular hydrogen bonds. Supersonic jet infrared (IR) and Raman spectra combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 41 publications
1
39
0
Order By: Relevance
“…It is important to mention that our most stable aldehyde conformer optimized in PCM-water (PCM:p olarizablec ontinuum model)h as as imilar structure to the most stable monomer (M4) of ref. [13] and to that of the ref. [12].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…It is important to mention that our most stable aldehyde conformer optimized in PCM-water (PCM:p olarizablec ontinuum model)h as as imilar structure to the most stable monomer (M4) of ref. [13] and to that of the ref. [12].…”
Section: Introductionmentioning
confidence: 84%
“…They also analyzed the IR and Ramans pectra with the help of ab initio calculations.G lycolaldehyde hasa lso been studied in the gas phase by different techniques, such as molecular beam microwave Fourier transform( MB-MWFT) spectroscopy [12] or supersonic jet infrared andR amant echniques. [13] Specifically,i nr ef. [13],t he authors:1 )showedt hat C 2 -symmetric dimers could be formed with intermolecular O-H···O = C bonds,w hile the corresponding intramolecular H-bondsw ere broken;2 )assigneds pectral bands to the vibrational movements of the M4 monomer ando ft he D8 and D4 dimers, being D8 the mosts table dimer;3 )suggested ar otational spectroscopic study of the most stable polar dimer,w hich is probablyt hermodynamically more stable than the chemically bound dimer;4 )reported that glycolaldehydes hows that cooperative hydrogen-bondp atterns can be superseded by isolated bonds if the geometric constraints are favorable for the latter,ac onclusion obtainedf rom an analysis supported by quantum chemical calculations of the O-H stretching range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the conditions of asupersonic expansion, non-covalently bound dimers are formed from isolated monomers (Figure 1c,d). [19] Recently,A ltnçder et al studied the glycolaldehyde dimer using FTIR-and Raman-spectroscopy under isolated conditions in am olecular jet. [19] They identified two conformers,w hich they assigned to aC 2 symmetric species consisting of two intermolecular hydrogen bonds and adimer consisting of one inter-a nd one intramolecular hydrogen bond, which is energetically less favored by about 5kJmol À1 .…”
mentioning
confidence: 99%
“…For a ISS⋯IRS interaction, “two oxygen atoms” from a substrate (say, qunione) molecule serve as information hub as it sequentially gains 2e − by electrochemical reduction process through linear scan ‐ cyclic voltammetric technique. As regards to molecular recognition, Dwek observed that the cells and bacteria generally use sugars to communicate . It is suggested that carbohydrates are not only suitable for conducting recognition process but also form a network or cage within a molecule which exhibits electronic communication.…”
Section: Figurementioning
confidence: 99%